Prevalent races of wheat rust pathogens in Lebanon, Morocco, and Tunisia in 2024 - Nazari, Kumarse; El Amil, Rola; Al-Jaboobi, Muamar; Maafa, Ilyass; Kemal, Seid Ahmed; SBAI, Ibtihel; Ramdhane, Nasraoui; Bouslimi, Abdelsattar (International Center for Agricultural Research in the Dry Areas, 2024)
During the 2024 rust surveys, wheat rust samples were gathered from farmer fields and research stations in CWANA including Lebanon, Morocco, and Tunisia using the RCRRC sampling kit. The Turkiye-ICARDA Regional Cereal Rust Research Center in Izmir received a total of 595 samples, with 88 from these three countries: 21 from Lebanon, 49 from Morocco, and 18 leaf rust samples from Tunisia. Severe drought prevented yellow rust observations in Morocco and Tunisia, but Lebanon's yellow rust samples were classified as PstS2+virYr27 and PstS17. Additionally, three stem rust races were identified: TKKTF in Lebanon, and TKTTF and TTTTF in Morocco. We were not able to retrieve the rust samples from Tunisia because of poor sampling and preservation conditions. There was more than 4 months before sampling and receiving samples to RCRRC. Leaf rust samples are currently undergoing race analysis following several purification steps.